Selecting sustainable packaging materials and strategies: a holistic approach considering whole life cycle and customer preferences - Mudgal, Devanshu; Pagone, Emanuele; Salonitis, Konstantinos (Elsevier, 2024)
With the increasing public awareness of packaging and the environmental impact caused by it, companies are driving their businesses to introduce and promote practices that help ease the negative impact of packaging on the environment. Studies done on consumer behaviour show that decisions nowadays are influenced by sustainability. Yet, companies struggle with changing practices and justifying adopting environmentally friendly packaging materials. The current paper presents a holistic approach, addressing the need for identifying, assessing, and selecting sustainable materials for packaging applications. The Kano model prioritises features that are then used with Ashby plots for identifying alternative materials. Life cycle assessment, as well as life cycle costing, are used for assessing the environmental and financial impact of the use of such materials. Automatically weighted Multi-Criteria Decision-Making Analysis (MCDA) is used to select the most appropriate packaging material. This methodology provides a combinatorial ranking for each criterion set by four pre-defined weight distributions for Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS). The proposed methodology allows for a systematic and holistic design process when deciding on packaging materials for any product. The methodology is validated for the case of packaging weather-sensitive cast stone products and carbonated drinks. In cast stone, three packaging materials are ranked for pallets based on their attributes. Similarly, for carbonated drinks, three packaging materials are recommended at the end of the study.
Keywords: 33 Built Environment and Design; 12 Responsible Consumption and Production; Environmental Sciences; 33 Built environment and design; 40 Engineering